An illustrated key and synopsis of the families and genera of carybdeid box jellyfishes (Cnidaria: Cubozoa: Carybdeida), with emphasis on the “Irukandji family” (Carukiidae) - Bentlage, B.; Lewis, C. (Journal of Natural History, 2012)
Box jellyfishes (Cnidaria: Cubozoa) have a profound impact on human activities because of their highly potent venoms that may lead to severe envenomations in humans. Cubozoa is one of the smallest classes within Cnidaria with only some 50 described species in seven families. The literature on Cubozoa is scattered and oftentimes difficult to access. In particular, comprehensive treatments of Cubozoa that present a comparative overview of the group are either non-existent or largely outdated. Here we provide a synopsis of the carybdeid Cubozoa (Carybdeida) including an illustrated key to the families and genera of this order. Of particular interest is the family Carukiidae, which contains the species that was originally attributed with causing a severe envenomation syndrome called Irukandji syndrome. One new species of Carukiidae, Malo filipina sp. nov., is described, Morbakka virulenta is redescribed and a neotype is designated, and an unidentified species of Morbakka is recorded from the Philippines.